Physical Activity and Nutrition Program for Seniors (PANS): Process Evaluation. Issue 4 (July 2013) - Burke, Linda; Jancey, Jonine M.; Howat, Peter; Lee, Andy H.; Shilton, Trevor
Issue addressed . The Physical Activity and Nutrition Program for Seniors (PANS) program aimed to increase levels of physical activity and improve the diet of insufficiently active community-based seniors aged 60 to 70 years using a range of strategies. Comprehensive process evaluation was used to determine the suitability and appropriateness of the resources and effectiveness of the strategies. Method . Process evaluation data (qualitative and quantitative) were collected on the program strategies and resources throughout, and at the conclusion of the intervention period. Results . The program strategies/resources were found to be relevant to the population, assisting participants to increase their level of physical activity and improve their diet. Participants reported that the program resources were suitable for their age-group (84%), encouraged them to think about physical activity (78%), and nutrition (70%). Participants reported that they used the pedometer (91%) and recorded daily steps (78%). Moreover, the provision of group guides facilitated individuals to set and achieve personal goals. Conclusion . The PANS strategies and resources were appropriate, which supported the seniors in identifying, establishing, and achieving their physical activity and nutrition goals. Minor refinements of the program were recommended based on the findings.